Pengembangan Tes Diagnostik Untuk Materi Gaya Pembelajaran IPA Kelas IV SD Daarul Qur’an International - Amrina, Pebrisa (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research is caused by students' obstacles in understanding science learning materials. This problem must be solved through diagnostic testing. One of the problems identified is due to misconceptions, which are introduced as misconceptions. These misconceptions can be identified by using a tool called Confidence Response Index (CRI), which detects misconceptions and lack of understanding among students. The purpose of this study was to develop a diagnostic tool and a valid CRI test model for elementary school students. This research is a development research using the 4-D model. The stages of this research consisted of planning, designing, developing, and disseminating. Dissemination was not continued in this study. The research found that the implementation of diagnostic tests and CRI obtained the results, namely the validation sheet of the lesson plan by the validator according to the criteria of very valid, the validation sheet of the learning outcomes test by the validator the criteria of a very valid category, the instrument sheet assessing the validity of diagnostic test questions with CRI by the validator with the valid category. Diagnostic tests using CRI obtained results explain almost every question students have misconceptions.